Early Diagnosis of Hip Joint Involvement of Ankylosing Spondylitis Using Magnetic Resonance Imaging in the Absence of Clinical and X-Ray Findings - Gökhan SÖKER; Bozkurt GÜLEK; Müge AYDIN TUFAN; Eda SÖKER; Bayram KELLE; Agah Bahadır ÖZTÜRK (Archives of Rheumatology, 2014)
Objectives: This study aims to describe magnetic resonance imaging (MRI) findings of hip joint involvement in ankylosing spondylitis (AS) in the absence of clinical and X-ray signs. Patients and methods: Between January 2012 and June 2012, 23 patients with AS without hip pain symptoms who were admitted to Adana Training and Research Hospital, Department of Physical Therapy and Rheumatology were included in the study. The control group consisted of 20 healthy individuals. All patients underwent MRI examination of both hips. Results: Of 23 patients, 10 (43.4%) had a pathological finding in at least one of the two sides based on the MRI findings. Seven patients demonstrated unilateral, and three patients demonstrated asymmetrically bilateral involvements. Bone marrow edema was present in six out of the 46 hip joints (13%). Eleven hip joints (24%) showed synovial fluid. One patient had bone marrow edema together with a subchondral cyst, while another patient demonstrated a combination of bone marrow edema and tendinitis. Conclusion: There may be hip joint involvement in AS patients even in the absence of clinical and X-ray signs. Early detection of bony abnormalities may prevent both the damage to the bone and the development of ankylosis.